Impact of the 2023 ACR/EULAR antiphospholipid syndrome criteria in 1200 women with prior obstetric antiphospholipid syndrome - Alijotas-Reig, Jaume; Esteve-Valverde, Enrique; Sáez-Comet, Luis; Anunciación-Llunell, Ariadna; Ferrer-Oliveras, Raquel; Lefkou, Eleftheria; Mekinian, Arsène; Belizna, Cristina; Hoxha, Ariela; Tincani, Angela; Marozio, Luca; Espinosa, Gerard; et al. (Elsevier BV, 2026)
Aim: The goal of a high specificity led to a loss of sensitivity in the new 2023 ACR/EULAR APS classification criteria, and mainly affecting obstetric clinical phenotype (OAPS). To reclassify a cohort of 1,200 women diagnosed of OAPS based on the Sydney classification criteria by applying the 2023 ACR/EULAR APS criteria.
Methods: The European Registry on Obstetric Antiphospholipid Syndrome (EUROAPS) with 1,200 women that fulfil the Sydney classification criteria were reanalysed according to the obstetric (domain 4) and laboratory domain 8 of the new classification criteria.
Results: When our cases were re-classified by applying the clinical criteria of domain 4, 816 cases (68%) would be excluded, leaving 384 cases (32%). The criteria that moderate to high IgM positivity is insufficient to classify patients, it led to a drop of additional 46 women, with a final number of excluded cases of 862 (71.83%), leaving only 338 cases (28.17%). Furthermore, the implementation of 40 units threshold discarded 86 women with an antiphospholipid antibody positivity above the 99th percentile cutoff. Eventually, from the 1,200 cases initially classified by the Sydney criteria, only 256 (21,33%) will remain.
Conclusion: The 2023 ACR/EULAR classification criteria substantially reduce the proportion of women with prior obstetric APS who remain classifiable in our cohort. Although these findings highlight a marked decrease in case identification compared with the Sydney criteria, the potential clinical and research implications of this reduction warrant further evaluation in prospective studies.